Unfavorable critical moments and way of facing them from the futsal coach's point of view through ad hoc questionnaire. [Momentos críticos desfavorables y manera de afrontarlos desde la perspectiva del entrenador de futsal a través de un cuestionario ad hoc]. - Cesar Méndez-Domínguez; Miguel Angel Gómez-Ruano; Luis Miguel Ruiz-Pérez; Yixiong Cui (Ramón Cantó Alcaraz, 2017)
In this study, a designed ad hoc questionnaire was constructed and validated to investigate the opinion of coaches about the concept of unfavorable critical moment in futsal, and the coincident use of goalkeeper as an outfield player strategy (5vs4) with that critical moment, which is a decisive step towards theoretical and methodological convergences. A total of 129 coaches belonging to teams of divisions 1st, 2nd and 2nd B participated in the questionnaire, which was validated by the judgment of experts thru calculating the content validity through the Aiken's V coefficient (Aiken, 1980, 1985). The results of the qualitative study revealed the importance that futsal coaches give to the maximum difference of 2 goals, and to the last 8 min of the game as maximum exponents of criticality, also to the importance of the 5th accumulated foul as a precipitant factor of an unfavorable critical moment in maximum equality matches. In addition, coaches manifested that interactive effects of score-line, remaining time and accumulated fouls could be the trigger of unfavorable critical moments, and using the goalkeeper as an outfield player strategy is a common practice to solve these situations. The values obtained in 19 of the 20 items (V> 0.90) attest that the content of the questionnaire is valid to show that the sample of futsal coaches understands the concept of criticality. The implications of the study contribute to a more specific knowledge of the futsal game and at the practical level the possibility of using this information to establish training objectives related to different stress conditions. Resumen A través de la construcción y validación de un cuestionario diseñado ad hoc se trató de investigar el pensamiento del entrenador relacionado con el concepto de momento crítico desfavorable en futsal, y la utilización del portero-jugador (5vs4) coincidente con el momento crítico, como un paso decisivo hacia convergencias teóricas y metodológicas. Un total de 129 entrenadores pertenecientes a equipos de 1ª, 2ª y 2ª B participaron en el cuestionario, que fue validado mediante el juicio de expertos calculando el índice de validez de contenido a través del coeficiente Aiken's V (Aiken,1980, 1985). Los resultados del estudio cualitativo revelan la importancia que otorgan los entrenadores de futsal a la diferencia máxima de 2 goles y a los últimos 8 minutos del partido como máximos exponentes de la criticidad, y a la importancia de la 5ª falta como factor precipitante de un momento crítico desfavorable en partidos de máxima igualdad. Además, muestran acuerdo en que los efectos interactivos de marcador, tiempo y faltas pueden ser el desencadenante de los momentos críticos desfavorables, y que es una práctica común el decidir afrontarlos con la utilización del procedimiento portero como jugador de campo (5vs4). Los valores obtenidos en 19 de los 20 ítems (V> 0.90) atestiguan que el contenido del cuestionario es válido para demostrar que la muestra de entrenadores de futsal entiende el concepto de criticidad. Las implicaciones del estudio aportan la contribución esencial del entrenador para un conocimiento más específico del juego, y a nivel práctico la posibilidad de utilizar esta información para establecer objetivos de entrenamiento relacionados con las diferentes condiciones de estrés.